Multi-dimension Integrated Electronic Commerce Trust Model Based on Interval-valued Intuitionstic Fuzzy - ZHONG Lin,ZHANG Jian,LIANG Jianhai (Ji suan ji gong cheng, 2019)
Most existing electronic commerce trust algorithms ignores the uncertainty of consumers’ subjective preference and dosn’t consider language evaluation information.To solve the problem,a multi-dimension integrated trust model is proposed.Multi-dimension trust feedback information is integrated into interval-valued intuitionistic fuzzy numbers.Based on Technique for Order Preference by Similarity to Ideal Solution (TOPSIS),the neartude between the interval-valued intuitionsic fuzzy numbers and the ideal intuitionsic fuzzy numbers is calculated,and the trust of service entities is ranked according to the neartude.To prevent the internet fraud,the penalty term is added into the model.The simulation results show that the decision-makers’ risk preference,the quantitative and qualitative evaluation information are taken into consideration in the model,and its anti-fraud ability is better than the interval-valued cloud model.